2022
DOI: 10.1007/s00737-022-01213-z
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms during pregnancy and after birth in women living in Sweden who received treatments for fear of birth

Abstract: The aim of this study was to investigate the prevalence of depressive symptoms and associated factors in women who underwent treatments for fear of birth; internet-based cognitive therapy, counseling with midwives, continuity with a known midwife or standard care. A secondary analysis was performed using data collected from four samples of women identified with fear of birth and receiving treatment with different methods. A questionnaire was used to collect data in mid-pregnancy and at follow-up 2 months after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 47 publications
0
13
1
Order By: Relevance
“…(2) different assessment criteria and different evaluation time points led to a different assessment result of the incidence of PPD and PPA. 5,6,21 In the current study, EPDS and STAI6 scores were used to evaluate PPD and PPA at 6 weeks after women gave birth, among which, EPDS score was the most common worldwide used screening tool for PPD, and the STAI6 score was convenient to evaluate PPA. 19,20,22 In terms of the association of T-helper cells and their related cytokines with depression and anxiety, it has been reported that Th1 and Th2 cells are dysregulated in patients with depression 23 ; besides, an interesting study illustrates that Th17 cells are increased in depressed patients 11 ; meanwhile, it also has been presented that IL-17A is elevated but IFNγ and IL-4 are normal in depressive patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…(2) different assessment criteria and different evaluation time points led to a different assessment result of the incidence of PPD and PPA. 5,6,21 In the current study, EPDS and STAI6 scores were used to evaluate PPD and PPA at 6 weeks after women gave birth, among which, EPDS score was the most common worldwide used screening tool for PPD, and the STAI6 score was convenient to evaluate PPA. 19,20,22 In terms of the association of T-helper cells and their related cytokines with depression and anxiety, it has been reported that Th1 and Th2 cells are dysregulated in patients with depression 23 ; besides, an interesting study illustrates that Th17 cells are increased in depressed patients 11 ; meanwhile, it also has been presented that IL-17A is elevated but IFNγ and IL-4 are normal in depressive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the incidence of PPD and PPA, it has been reported that 19.2% women suffer from PPD during the first 3 months after giving birth 6 ; furthermore, 19% Sweden women experience PPD after 2 months postpartum 5 ; additionally, another interesting study also illustrated that the incidence of PPD ranges from 9% to 12% among women during postpartum 21 . In the current study, the incidence of PPD and PPA were 24.3% and 27.9%, respectively, which was numerically higher than in previous studies 5,6,21 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations